Constructing the Image of "Japanese People": A Study on the Translation of the Japanese Children's Anthology Children of the Base from a Paratextual Perspective. - Wang, Luer; Lin, Zibo (Children's Literature in Education, 2026)
Towards the end of World War II in Japan, social conflicts exacerbated by the presence of American troops became increasingly acute, leading to a rise in the "anti-US military base movement". Concurrently, there was a revival of the pre-war folk education movement known as "life composition education", resulting in the publication of numerous collections of children's compositions that depicted everyday life. The intersection of these two social movements led to the creation of the children's anthology Children of the Base in the 1950s. This anthology, which reflected the lives and social issues faced by those living near American military bases, was translated into Chinese with support from the Chinese People's National Committee for Children's Defense, under the leadership of Qingling Song. The Chinese translation utilized various paratextual elements, such as the cover, foreword, illustrations, accompanying text, and translator's notes, to emphasize the Japanese people's attitude of resistance. This effort not only expressed China's intent to unite Japan's progressive forces and foster friendly exchanges between the two nations but also illustrated China's ideological perspective on the "Japanese people" within the framework of "People's Diplomacy".